A naval damage incident recoverability toolset: Assessing naval platform recoverability after a fire event. (1st July 2020) - Woolley, Anthony; Ewer, John; Lawrence, Peter; Deere, Steven; Travers, Anthony; Whitehouse, Tom; Galea, Edwin Richard
Abstract: Naval platform survivability is a key enabler to ensure maritime warfighting capability. Therefore, assessment of naval platform recoverability, after a damage event, is critical to assure platform survivability in a warfighting environment. To support such an assessment, an innovative modelling and simulation capability, known as the Naval Damage Incident Recoverability Toolset ( NavDIRecT ) is being developed. NavDIRecT is being designed as a component-based, open architecture providing the necessary framework to allow analysts to integrate domain models of their choosing. NavDIRecT will facilitate analysis of warfighting and peacetime damage events using a variety of mathematical models, thereby avoiding the limitations of other survivability assessment techniques. Development of NavDIRecT is exemplified by integrating the human movement simulator, maritimeEXODUS, the fire simulation environment, SMARTFIRE, and a three-dimensional naval platform model. NavDIRecT will enable analysis of crew interaction with damage events, thereby allowing acquisition programs and mission planners to examine platform survivability with respect to mission capability requirements. The impetus for NavDIRecT development is for assessment of naval platform survivability and mission success; however, the tools and techniques are equally suitable for use in incident management, training, and analysis of merchant and commercial shipping in accordance with the Safety of Life at Sea (SOLAS). Highlights: Presents the importance of recoverability for maritime platform survivability. Proposes a simulation capability to assess maritime platform recoverability. Presents development of a unique recoverability assessment capability. Demonstrates current state of the recoverability assessment capability. Presents emergent fire simulation capability resulting from this research.